(untitled) (RELACult - Revista Latino-Americana de Estudos em Cultura e Sociedade, 2021)
This article examines two emblematic musical forms that are found in the border regions of Portugal: chromatic accordion music in the Algarve in southern Portugal, and diatonic concertina music in northern Portugal. The object of this text is to reveal the processes of development and transmission of these border-area traditions, as well as reveal efforts to conceive these traditions as Cultural Heritage, whether it be on a local, national or supranational level, and the motivations of those efforts. The methodology employed in this study involved in situ oral history collection, and field work was carried out in 2019 and 2020 in various communities in the interior of Portugal. A comparison is made of the two case studies, paying attention to the ways in which these traditions have been fomented and projected as being representative of a region or nation, and also paying attention to the role played throughout history by migratory diasporas (provoked by political, economic and demographic factors) in the transformation, resignification, and projection of these traditions.